2012
DOI: 10.1161/hypertensionaha.111.190140
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-Ribose) Polymerase 1 Inhibition Improves Coronary Arteriole Function in Type 2 Diabetes Mellitus

Abstract: Type 2 diabetes (T2D) is associated with microvascular dysfunction. We hypothesized that increased Poly - (ADP-ribose) polymerase-1 (PARP-1) activity contributes to microvascular dysfunction in T2D. T2D (db-/db-) and non-diabetic control (db-/db+) mice were treated with two different PARP-1 inhibitors (INO-1001, 5 mg/Kg/day and ABT-888, 15 mg/Kg/day) for two weeks. Isolated coronary arterioles (CA) were mounted in an arteriograph. Pressure-induced myogenic tone (MT) was significantly potentiated, while endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 39 publications
(44 reference statements)
3
36
0
Order By: Relevance
“…We and other investigators showed an increase in myogenic tone in type 2 diabetes (12,25). In this study we demonstrated that in type 2 diabetic mice, elevated myogenic response is a consequence of enhanced p22 phox expression since the downregulation of p22 phox by siRNA and ROS scavenger restored the myogenic tone in diabetic mice.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We and other investigators showed an increase in myogenic tone in type 2 diabetes (12,25). In this study we demonstrated that in type 2 diabetic mice, elevated myogenic response is a consequence of enhanced p22 phox expression since the downregulation of p22 phox by siRNA and ROS scavenger restored the myogenic tone in diabetic mice.…”
Section: Discussionsupporting
confidence: 66%
“…The vessels were pressurized to 50 mmHg using pressureservo control perfusion system (Living Systems Instruments, St. Albans, VT) for a 40-min equilibration period. The vessel diameter was monitored by a video image analyzer as previously described (9,12).…”
Section: General Protocol In Micementioning
confidence: 99%
“…The myogenic response is characterized by vasoconstriction in response to an increase of intraluminal pressure and vasodilatation in response to a decrease in intraluminal pressure and is an intrinsic vascular response that plays an important role in the local regulation of blood flow (Bayliss, 1902). Previous studies have shown that impaired small artery function is attributable to the enhanced myogenic response in diabetic animals (Lagaud et al 2001;Choi et al 2012;Kassan et al 2013). Interestingly, in the present study, we observed an enhanced myogenic response in the coronary arteries of type 2 diabetic mice associated with increased ER stress markers.…”
Section: Discussionmentioning
confidence: 99%
“…PARP-1, the DNA repair-associated nuclear enzyme, is involved in the development of various diabetic complications, including diabetic cardiomyopathy, diabetic nephropathy, diabetic cystopathy and diabetic retinopathy (23,34,35). Hyperglycemia can lead to overproduction of mitochondrial ROS, which then activates PARP-1 (13).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%